Exploring the Relationship between Energy Consumption and Economic Growth in Lower Middle and High Income Economies using Panel data Techniques - Fraz, Tayyab Raza (International Journal of Energy Economics and Policy, 2022)
In this paper, the panel relationship between energy consumption (ECP) and economic growth (GDP), is investigated for the thirty-one countries from 1971 to 2014. These countries are divided into two panels based on lower-middle-income and high-income-level economies. Traditional ADF unit root test is used to confirm the stationarity at first difference. Also, four panel unit root tests, namely LLC (2000), IPS (1997, 2003), Fisher (1999), and Hadri (2000) tests confirmed the stationarity of variables for both panels at first difference. Furthermore, the long-run relationship between ECP and GDP is explored by four advanced panel cointegration techniques, i.e., Kao (1999), Pedroni (1999, 2004), Fisher (1999), and Westerlund (2007). Moreover, the pairwise panel causality test is used to identify the Granger causality between ECP and GDP. Lastly, the dynamic OLS (DOLS) estimator of Saikkonen (1991) and the fully modified OLS (FMOLS) estimator of Phillips and Hansen (1990) is used to estimate the parameters of the cointegration relationship. According to the empirical results, ECP and GDP are cointegrated for both panels. Long-run Granger causality running from GDP to ECP for both income level economies is also revealed. The energy conservation policies can play a vital role in boosting economic growth, especially for lower-middle-income economies.